PENGARUH PRIVACY, BRAND NAME, DAN WORD OF MOUTH TERHADAP BRAND TRUST DAN BRAND COMMITMENT PADA PEMBELIAN GADGET SECARA ONLINE DI SURABAYA - MARDIANA, RIA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
strategy to achieve and the desired market share. For that the company can do this by having a dominant market brand. Through the brand would enhance consumer purchasing decision making process and also the consumer will be easy to differentiate the products they buy with the other competitors' products. This is an action must be able to be realized by the company mainly engaged in the sale through online sites such as the sale of gadgets. This study aims to determine the effect of privacy, brand name, word of mouth on brand trust and brand commitment in buying gadgets online at Surabaya. The population in this study all the people in Surabaya gadget ever buy products online. Sampling techniques in the study were non probability sampling using purposive sampling method. Purposive sampling is a non-probability sampling technique in which sample selection is based on certain considerations that the respondents who have bought products online gadget in Surabaya. Analyze technique using structural equation modeling (SEM). Based on the calculation results obtained that the Privacy influence on the purchase of brand trust online gadget in Surabaya. Brand name influence on brand trust in purchasing on-line gadget in Surabaya. Word of mouth effect on brand trust in purchasing on-line gadget in Surabaya. Brand trust affects brand commitment in an online purchase in Surabaya